First‐in‐human application of double‐stranded RNA bacteriophage in the treatment of pulmonary Pseudomonas aeruginosa infection - Linlin Li; Qiu Zhong; Yunze Zhao; Juan Bao; Bing Liu; Zhuojun Zhong; Jing Wang; Lan Yang; Tingting Zhang; Mengjun Cheng; Nannan Wu; Tongyu Zhu; et al. (Microbial Biotechnology, 2023)
Abstract A double‐stranded RNA (dsRNA) phage phiYY is able to kill a pyomelanin‐producing Pseudomonas aeruginosa strain, which was isolated from a 40‐year‐old man with interstitial lung disease (ILD) and chronic lung infection. Phage therapy was used as a last resort for this patient. The three‐course nebulized phiYY treatment was used to reduce the bacterial burden and clinical symptoms of the patient. Recurrences of P. aeruginosa infections were observed 1–3 days post phage therapy. The recurrent isolates exhibited distinct antibiotic‐susceptibility profiles compared with the original strain yet were still susceptible to phiYY. This assay represents the application of dsRNA phage in the treatment of chronic lung infection, albeit the safety and efficacy of the dsRNA phage require further assessment.